ABO Blood Groups Are Not Associated With COVID-19 Disease Incidence and Severity When Correcting for Ethnicity Differences in Blood Type. Issue 2 (11th April 2022) - Pasko, Bryce E; Abbott, Diana; Bocsi, Gregary T; Draper, Nicole L
Abstract: Objectives: To determine if blood type is a risk factor for coronavirus disease 2019 (COVID-19) disease incidence and severity after correcting for ethnicity differences between novel infections and known ABO blood type frequency differences. Methods: We performed a retrospective analysis on all severe acute respiratory system coronavirus 2 (SARS-CoV-2) infections and disease severity across two major testing sites in Colorado. We evaluated all individuals with a SARS-CoV-2 nucleic acid test (NAT) and a known blood type between March 1, 2020, and June 1, 2020. We then created a prediction algorithm based on the corrected blood types by ethnicity using data from the Colorado Department of Health and established blood types by ethnicity. We applied this prediction algorithm to all patients in our sample. Results: Of 8, 676 patients, 485 (5.6%) had a positive SARS-CoV-2 NAT test and 8, 191 (94.4%) had a negative test. All patients had ABO blood types that mirrored the expected blood type distribution within the state of Colorado ( P  = .15, χ  2 statistic = 5.31). No differences in expected blood groups were present between ethnicity-adjusted SARS-CoV-2–negative and SARS-CoV-2–positive patients (χ  2  = 3.416313, P  = .332). Conclusions: Blood type is not associated with COVID-19 disease incidence or severity after correcting for ethnicity differences in expected blood type frequencies.